Pencucian Uang, Eksploitasi Tenaga Kerja, dan Perdagangan Orang dalam Lingkar Judi Online: Sebuah Pendekatan Interdisipliner terhadap Kejahatan Transnasional di Asia Tenggara - Kamalludin, Iqbal (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2025)
The online gambling industry in Southeast Asia has become a strategic platform for transnational criminal syndicates to commit crimes such as money laundering, labor exploitation, and human trafficking. This study uses an interdisciplinary approach—including legal analysis, criminology, and social studies—to examine the involvement of Indonesian citizens (WNI) as the main victims in exploitation networks operating in countries such as Cambodia, Myanmar, and Malaysia. Although most of the literature and discussions reflect the broader Southeast Asian regional context, this research focuses specifically on the situation of Indonesian migrant workers. The study highlights the criminal methods employed by syndicates, regulatory weaknesses at both national and international levels, and the challenges facing effective cross-border cooperation. In addition, important aspects of increasing the capacity of law enforcement, especially in tracking digital transactions and protecting victims, are also discussed. The findings show that exploitation of Indonesian citizens occurs systematically and involves various actors across jurisdictions. Therefore, a comprehensive legal approach, stronger regional cooperation under ASEAN, and policies for the protection of migrant workers based on human rights are needed. The policy implications of this study focus on concrete steps that the Indonesian government can take to effectively respond to the complexity of this crime.